SimulationModel fortheCorrosionBehaviorofAdditively Manufactured Iron in Electrolytic Environment Using COMSOL Multi-physics - Sharma P.; Pathak D.K.; Gowerneni A. (My University, 2025)
The modelling of the corrosion behavior of additively manufactured iron (Fe) as biomaterials is the subject of this research work.The electrochemical interaction of metal in the electrolytic environment, such as screw plate couplings, initiates the biocorrosion process.The body tissues have an electrolytic characteristic due to the discharged ions, enzymes, and hormones, making the environment extremely active in terms of corrosion potential. As a result, it becomes very important to assess biometals’ toxicity and corrosion behavior by simulating the corrosion degradation process, which will focus on substitute biomaterial designs that might decrease or avoid corrosion degradation behavior’s effects.The corrosion potentials of the biometal couples of additively manufactured Fe material are compared in this work utilizing the finite element based COMSOL electrochemical analysis technique for a two-dimensional (2D) model in the electrolyte solution and a three-dimensional (3D) model in two distinct electrolytes of bone and muscle. The simulated Fe corrosion behavior findings are then compared to those of the experimental corrosion. The higher corrosion current density resulted in many active implants exhibiting a faster degradation of biodegradable porous Fe. © 2023 Sharma et al.